KEMAMPUAN DAYA HAMBAT EKSTRAK DAUN MURBEI (Morus alba) TERHADAP PERTUMBUHAN Aspergillus flavus - Yusril Hidayat, Aditya; Selamet Duniaji, Agus; Ayu Nocianitri, Komang (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 9 No 3 (2020): Jurnal ITEPA, 2020)
The aim of this research to determine the ability of mulberry leaf extract (Morus alba) to inhibit the growth of Aspergillus flavus. This research used completely Randomized Design with control treatment (without extract) and treatment of mulberry leaf extract concentration of 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, 100%. The experiment were repeated 2 times and resulting in 22 experimental units. The data were presented in descriptive statistic with tables, and figure. The results showed that the extract of mulberry leaf inhibit the growth of Aspergillus flavus with optimal concentration 80% with an average 11.95 mm and strong inhibition categories.